Implementasi Penguatan Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA Negeri 1 Wonosobo (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This thesis aims to: 1) find out the implementation of strengthening the learning of Islamic religious education and morals at SMA Negeri 1 Wonosobo; 2) to find out about programs of Islamic religious and moral education activities at SMA Negeri 1 Wonosobo; 3) to find out strategies for strengthening the learning of Islamic religious education and morals at SMA Negeri 1 Wonosobo; 4) to find out the supporting and inhibiting factors in strengthening the learning of Islamic religious education and morals at SMA Negeri 1 Wonosobo.This thesis uses a qualitative research approach where the type of research is descriptive. Data collection techniques using the method of observation, interviews and documentation. As for data analysis using data reduction, data presentation, and drawing conclusions.The results showed that: 1) The implementation of strengthening the learning of Islamic religious education and morals at SMA Negeri 1 Wonosobo is carried out almost every day and routinely, as a habituation activity to shape the character of students with noble character. 2) Programs to strengthen the learning of Islamic religious education and morals consist of routine daily programs, namely: congregational prayers, weekly routine programs, namely: Friday prayers, women's affairs, religious literacy every Friday morning, and KKI activities (Islamic study groups), and programs annual routine, namely: Maulid Nabi, isro' Mi'raj, and Ramadhan Islamic Boarding School. 3) Strategies carried out by the school in increasing student motivation using various models of methods, including lectures, discussions and questions and answers, and through pamphlets and social media. 4) The supporting and inhibiting factors of strengthening the learning of Islamic religious education and morals make the benchmark for the success of activities carried out in schools.